(untitled) (Journal of EAHIL, 2020)
The Researchers’ Gallery at Malmö University Library shows current research in exhibitions, co-created by librarians and researchers. The library invites all visitors to take part in and learn more about the research process and outcome. In an academic yet informal setting, the library offers a credible space for research communication. The Researchers’ Gallery is a space for students, researchers and the society to meet, and encourage cross-border knowledge creation. The Researchers’ Gallery has become a platform for continuing collaboration between researchers and between researchers and librarians. Exhibited research now has a natural and an integrated place in the learning environment of the library and at the university.